In vitro bioactivity and cytocompatibility properties of spark plasma sintered HA‐Ti composites1. Issue 2 (20th December 2012) - Kumar, Alok; Dhara, Sharmistha; Biswas, Krishanu; Basu, Bikramjit
Abstract: The present study reports the results of the detailed in vitro bioactivity and cytocompatibility properties of the hydroxyapatite (HA) and the HA‐titanium (HA‐Ti) composite with varying amount of Ti (5, 10, and 20 wt %), densified using spark plasma sintering process (SPS). Using this technique and tailoring suitable processing parameters, it has been possible to retain both HA and Ti in the sintered ceramics. Importantly, the uniquely designed SPS processing with suitably chosen parameters enables in achieving better mechanical properties, such as higher indentation fracture toughness (∼1.5 MPa m 1/2 ) in HA‐Ti composites compared with HA. X‐ray diffraction and scanning electron microscopic (SEM) observations reveal good bioactivity of the HA‐Ti composites with the formation of thick, flaky, and porous apatite layer when immersed in simulated body fluid at 37°C and pH of 7.4. Atomic absorption spectroscopic analysis of the simulated body fluid solution reveals dynamic changes in Ca +2 ion concentration with more dissolution of Ca +2 ion from the HA‐20Ti composite. However, the measurements with inductively coupled plasma spectrometer do not record dissolution of Ti +4 ions. Transmission electron microscopic analysis indicates weak crystalline nature of the apatite and confirms the formation of fine‐scale apatite crystals. MTT assay, fluorescence, and SEM study demonstrate good cell viability and cell adhesion/proliferation of the Saos ‐2 cells, cultured on the developed composites under standard culture condition, and the difference in cell viability has been discussed in reference to substrate composition and roughness. Overall, HA‐Ti composites exhibit comparable and even better in vitro bioactivity and cytocompatibility properties than HA. © 2012 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 2013.